IMPLEMENTASI LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK SELF-MANAGEMENT TERHDAP KEDISIPLINAN PESERTA DIDIK KELAS VII DI MTS USWATUN HASANAH PADALARANG - Rival Fauzan Izzul Haq; Nandang Rukanda; Muhammad Rezza Septian (IKIP Siliwangi, 2023)
This study aims to determine the implementation of group guidance services through self-This article aims to determine the implementation of group guidance services through self-management techniques on student discipline at MTs Uswatun Hasanah Padalarang. The research method used was descriptive qualitative, the subjects in this study were 4 students of class VII at Mts Uswatun Hasanah, this research instrument used observation, interviews and documentation guidelines and used data triangulation, namely data reduction, presentation, and drawing conclusions. The results obtained indicate that group guidance services through self-management techniques on student discipline have proven effective. Student responses to group guidance services through self-management techniques on student discipline carried out by researchers are giving positive responses, which means students are interested and happy to carry out group guidance services with BK teachers and researchers.Keywords:group guidance, self-management, discipline